PENGARUH MOTIVASI KERJA DAN BEBAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT. BANK CENTRAL ASIA TBK CABANG KALIMALANG - Hery Wihasnanto; Azbi Salsabilla Anshar (Jurnal Ekonomi dan Industri, 2024)
The purpose to analyze the influence of work motivation and workload on employee job satisfaction of PT. Bank Central Asia Tbk Cabang Kalimalang. The population in this study were employees of PT. Bank Central Asia Tbk Cabang Kalimalan,. The analytical method uses simultaneous and partially linear regression analysis. The results showed that in simultaneous or partially ways the work motivation and workload have a positive and significant effect employee job satisfaction of PT. Bank Central Asia Tbk Cabang Kalimalang.